A biocompatible gel probe based on three-core spinning technology and a preparation method thereof
The biocompatible gel probe prepared by the three-core spinning technology adopts a composite cortex and multi-layer functional core design, which solves the problems of high impedance, low conductivity and insufficient biocompatibility of existing electrode probes, and achieves high-sensitivity signal transmission and long-term stability, making it suitable for neurophysiological research and clinical neural interfaces.
Patent Information
- Application Number
- CN202511128999.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-08-13
AI Technical Summary
Existing electrode probes suffer from problems such as high impedance, low conductivity, mechanical properties that are incompatible with soft tissue, insufficient biocompatibility, and poor interface stability in neurophysiological signal acquisition, making it difficult to meet the requirements of high-sensitivity signal transmission and long-term application.
A biocompatible gel probe was prepared using a three-core spinning technique. The composite skin was composed of a sodium alginate-polydopamine-chitosan graft copolymer, and the three functional core layers were carbon nanotube-polyaniline nanosheets, graphene-polypyrrole-boron nitride nanosheets, and polythiophene-hydroxyapatite nanocrystal hybrid materials, respectively. A stable structure was formed through spinning, solidification, and curing processes, and the surface was modified with polyethylene glycol to improve interfacial bonding and biocompatibility.
It achieves low impedance, high conductivity, mechanical properties that match soft tissue, and high biocompatibility. It can simultaneously acquire signals from multiple targets, reducing the risk of mechanical damage and inflammation during electrode implantation. It is suitable for neurophysiological research and clinical neural interface technology.
Smart Images

Figure CN120616551B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of functional composite probe material preparation, in particular to a biocompatible gel probe based on three-core spinning technology and a preparation method thereof. BACKGROUND
[0002] The accurate collection and transmission of neural electrophysiological signals is a key link in neuroscience research and clinical treatment, which requires the electrode probe to have the ability of efficient bidirectional communication with the nervous system. Traditional electrodes used in this field are mostly made of noble metals such as gold, platinum, iridium or crystalline silicon, etc. Although these materials have certain conductivity, they have significant defects. The high impedance characteristic leads to large noise interference during signal collection, making it difficult to capture weak neural electrical signals; the low charge injection capacity limits the effective transmission of stimulation signals; more importantly, the mechanical properties of these materials are quite different from soft tissues, and mechanical damage is easily caused after implantation, and long-term use can cause inflammatory reactions and scar tissue formation, further hindering signal transmission, and seriously affecting their application in long-term neural interfaces.
[0003] To solve the above problems, researchers have developed flexible electrodes based on carbon-based materials, such as carbon nanotubes and graphene, in an attempt to improve the mechanical matching through the flexibility of the material. However, existing carbon-based electrodes are mostly single-core structures or simple skin-core structures, which still have obvious shortcomings. Single-core structures rely on a single conductive material, and the conductivity is limited by the performance of the material itself, making it difficult to meet the high sensitivity signal transmission requirements; in simple skin-core structures, the interface between the skin layer and the core layer is weakly bonded, and peeling off easily occurs during implantation or use, leading to electrode failure; at the same time, the skin layer material is mostly a single polymer, and the biocompatibility design is insufficient, still having the risk of inflammation, and the core layer lacks a multi-channel design, making it impossible to achieve simultaneous collection and differentiation of multi-target point signals.
[0004] At present, how to construct a multi-channel electrode probe with low impedance and high conductivity, mechanical properties matching soft tissue, high biocompatibility and stable interface is still a technical problem to be solved in this field. The existing technology cannot meet all these performance requirements at the same time, limiting the in-depth study of neural electrophysiology and the development of related clinical technologies, so a new electrode structure and preparation process need to be developed to break through the existing technical bottlenecks. SUMMARY
[0005] (I) Technical problems solved
[0006] In view of the deficiencies of the prior art, the present application provides a biocompatible gel probe based on three-core spinning technology and a preparation method thereof.
[0007] (II) Technical solutions
[0008] A biocompatible gel probe based on three-core spinning technology, the gel probe comprises a composite skin layer and a three-layer functional core layer, the composite skin layer is composed of a sodium alginate-polydopamine-chitosan graft copolymer, the mass ratio of sodium alginate, polydopamine and chitosan is 2:1:0.5, and the skin layer contains Chondroitin sulfate and Polyethylene oxide; sodium alginate provides a gel network skeleton for the cortex, polydopamine enhances the interfacial bonding between the cortex and the core layer through catechol groups, chitosan improves the biocompatibility of the cortex, chondroitin sulfate reduces inflammatory responses, and polyethylene oxide enhances the flexibility of the cortex;
[0009] The three functional core layers are the first core layer carbon nanotube-polyaniline Nanosheet hybrid material, second core layer graphene-polypyrrole-boron nitride nanosheet hybrid material and third core layer Polythiophene-hydroxyapatite nanocrystalline hybrid material, the mass ratio of carbon material, conductive polymer and new nanomaterial in each core layer is 1:2:0.3; carbon nanotubes, graphene and MXene are used as the core conductive matrix, polyaniline, polypyrrole and polythiophene enhance the conductivity of the core layer, Nanosheets, boron nitride nanosheets, and hydroxyapatite nanocrystals synergistically enhance the mechanical strength and conductive stability of the core layer;
[0010] The diameter ratio of the skin layer to the three-layer core layer is 1:0.28:0.22:0.17;
[0011] The deacetylation degree of chitosan in the composite cortex is ≥90%, and the molecular weight is 50,000-80,000 Da; the molecular weight of chondroitin sulfate is 30,000-50,000 Da, and the molecular weight of polyethylene oxide is 200,000-300,000 Da;
[0012] The aspect ratio of carbon nanotubes in the first core layer is 50-100, and the thickness of MoS2 nanosheets is 0.8-1.2nm; the diameter of graphene sheets in the second core layer is 5-10μm, and the lateral size of boron nitride nanosheets is 1-3μm; the MXene in the third core layer is , the aspect ratio of hydroxyapatite nanocrystals is 3-5.
[0013] Preferably, the thickness of the composite skin layer is 70-90 μm and the viscosity of the sodium alginate is , which can maintain the stability of the gel structure, the molecular weight of polydopamine is 7000-9000Da, ensuring the interfacial reaction activity; the diameter of the first core layer is 25-30μm, the diameter of the second core layer is 20-25μm, the diameter of the third core layer is 15-20μm, and the overall diameter is 150-200μm, which is adapted to the size of neurons.
[0014] Preferably, the first core layer has an electrical conductivity of 80-120 S / cm, the second core layer has an electrical conductivity of 70-100 S / cm, and the third core layer has an electrical conductivity of 50-80 S / cm, meeting the needs of electrical physiological signal transmission; the Young's modulus of the gel probe is 1.0-1.8 MPa, matching the mechanical properties of soft tissues, and the elongation at break is 25%-35%, avoiding breakage during implantation.
[0015] Preferably, The purity of the nanosheet is ≥99%, reducing the interference of impurities on conductivity, the number of layers of the boron nitride nanosheet is 3-5, enhancing the insulation barrier of the core layer, the nanocrystalline grain size of the hydroxyapatite is 50-100 nm, improving the affinity with biological tissues; the degree of polymerization of the conductive polymer in each core layer is 500-1000, ensuring the continuity of the conductive chain.
[0016] Preferably, the surface is modified with a polyethylene glycol layer, the molecular weight of the polyethylene glycol is 4000-6000 Da, the water contact angle after modification is 30-40 degrees, the modification density is 0.1-0.3 mg / cm2, and the anticoagulant property is improved.
[0017] Preferably, the swelling degree of the composite skin layer is 200%-300%, maintaining a humid environment, and the degradation rate in phosphate buffer solution is ≤5% in 24 hours, ensuring long-term stability; the stability of the core layer material is ≥95% in 24 hours under the same conditions, ensuring the durability of the electrical properties.
[0018] Preferably, the preparation method of the biocompatible gel probe based on the three-core spinning technology comprises the following steps:
[0019] S1. Preparing a composite skin layer spinning solution: dissolving sodium alginate in deionized water, stirring at 35°C for 1 hour to form an initial gel network, adding polydopamine and continuing to stir for 15 hours to promote the activation of the o-diphenol group, and then adding chitosan, chondroitin sulfate, and polyethylene oxide, stirring at 25°C for 10 hours to uniformly disperse the components, obtaining a uniform spinning solution;
[0020] S2. Preparing a first core layer spinning solution: dispersing carbon nanotubes in deionized water, ultrasonicating for 4 hours to open the agglomeration, adding polyaniline, and nanosheets ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate, stirring at 30°C for 12 hours, and the ionic liquid promotes the dispersion and interfacial bonding of the conductive substances;
[0021] S3. Preparing a second core layer spinning solution: dispersing Graphene dispersed in deionized water, ultrasonic for 3 hours to obtain single-layer dispersion, add Polyacetylene, Boron nitride nanosheet and Ionic liquid 1-ethyl-3-methyl imidazole tetrafluoroborate, 30℃ stirring for 12 hours, boron nitride nanosheet reduces signal interference of conductive area;
[0022] S4. Preparation of the third core layer spinning solution: the dispersed in deionized water, ultrasonic for 3 hours to maintain the sheet structure, add Polythiophene, Hydroxyapatite nanocrystal and Ionic liquid 1-hexyl-3-methyl imidazole bis-trifluoromethanesulfonimide, 30℃ stirring for 12 hours, hydroxyapatite nanocrystal enhances the interface adaptation of the core layer to the biological tissue;
[0023] S5. Three-core spinning: adopt transverse coaxial needle, outer tube inner diameter 280μm, middle tube inner diameter 150μm, inner tube inner diameter 100μm, length ratio of outer tube, middle tube and inner tube 1:0.8:0.7; the skin layer spinning solution is injected into the outer tube, the first core layer liquid is injected into the outer layer of the middle tube, the second core layer liquid is injected into the middle layer of the middle tube, and the third core layer liquid is injected into the inner tube, the extrusion speed is 1.2mL / h; the coagulation bath contains Calcium chloride, Dopamine and Magnesium chloride, temperature 25℃, calcium chloride promotes the rapid gel formation of the skin layer, and dopamine enhances the crosslinking of the skin layer;
[0024] S6. Drawing and solidification: the nascent fiber passes through a 2m solidification channel at a speed of 10cm / min, and the channel contains Calcium chloride solution, temperature 38℃, drawing ratio 1.4 times, solidification time 25 minutes, drawing improves the ordered arrangement of the core layer conductive substance, and high temperature promotes the interface reaction between the skin layer and the core layer;
[0025] S7. Washing and drying: deionized water washing 5 times to remove residual salts, 38℃ vacuum drying for 20 hours to fix the structure;
[0026] S8. Surface modification: the dried probe is soaked in Polyethylene glycol in Ethanol solution, solution pH 7.2, 25℃ ultrasonic for 3 hours at 18kHz, ethanol assists the penetration of polyethylene glycol, and ultrasonic promotes the uniform coverage of the modified layer; ethanol washing 5 times, 38℃ vacuum drying for 12 hours to form a stable modified layer.
[0027] Preferably, the distance between the outer tube and the middle tube of the transverse coaxial needle in step S5 is 90μm, and the distance between the middle tube and the inner tube is 50μm, which ensures that each layer is uniformly wrapped, and the stirring speed of the coagulation bath is 150r / min, so that the fiber is uniformly stressed.
[0028] Preferably, the solution flow rate in the curing channel in step S6 is 0.6 m / min, and temperature control is performed in sections: the first section is 30 DEG C, the second section is 38 DEG C, and the third section is 40 DEG C, and the length ratio of each section is 1:2:1; the temperature control in sections gradually enhances the cross-linking, and structural damage is avoided.
[0029] Preferably, the polyethylene glycol solution in step S8 contains The succinimidyl ester activator promotes covalent binding with the skin layer, the ultrasonic power is 250 W, the modification efficiency is improved, the zeta potential of the probe surface after modification is -20 to -15 mV, and cell adsorption is reduced.
[0030] (Three) beneficial technical effects
[0031] Compared with the prior art, the beneficial effects of the present application are:
[0032] 1. The three-layer functional core layer adopts a carbon nanotube-polyaniline-MoS2, graphene-polyazole-boron nitride, MXene-polythiophene-hydroxyapatite hybrid system, the carbon material provides a high-conductivity foundation, the conductive polymer enhances charge transfer, and the nanomaterial optimizes the conductive network, the synergistic effect of the three greatly reduces the electrode impedance, improves the conductivity, meets the collection and transmission requirements of high-sensitivity nerve signals, and the three-core structure realizes multi-channel design and can simultaneously distinguish signals of different target points.
[0033] 2. The composite skin layer takes sodium alginate as a skeleton, and is composed of polydopamine, chitosan, chondroitin sulfate and polyethylene oxide, which not only endows the skin layer with a Young's modulus matched with soft tissues and good flexibility, avoids implantation damage, but also forms stable covalent bonding with the core layer through the catechol group of polydopamine, solves the problem of interface peeling of the traditional skin-core structure, and ensures the structural stability of the electrode during long-term use.
[0034] 3. The chitosan and chondroitin sulfate in the skin layer can inhibit inflammatory reactions, the surface polyethylene glycol modification reduces protein adsorption and cell rejection, the hydroxyapatite nanocrystals in the core layer improve the affinity with biological tissues, and the synergistic effect of multiple components significantly improves the biocompatibility of the electrode and reduces the risk of long-term implantation. In addition, the three-core spinning process can be continuously carried out at room temperature, the operation is simple, the size and performance of each layer can be easily controlled, and the process is suitable for large-scale production, thereby providing a new type of high-performance tool for neural electrophysiological research and clinical neural interface technology. BRIEF DESCRIPTION OF DRAWINGS
[0035] Fig. 1 It is a preparation method flow chart of a biocompatible gel probe based on a three-core spinning technology disclosed by the present application;
[0036] Fig. 2 It is a columnar broken line comparison graph of conductivity and surface resistance of examples and comparative examples.
[0037] Fig. 3 is the breaking elongation and 24-hour cell survival rate of the examples and comparative examples;
[0038] Fig. 4 is the radar chart of the performance parameter results of the examples and comparative examples after unified dimensioning. DETAILED DESCRIPTION
[0039] According to Figs. 1 to 4 , the specific embodiments of the present application are as follows:
[0040] I. Technical principle
[0041] The biocompatible gel probe based on three-core spinning technology realizes low impedance signal transmission, mechanical property matching with soft tissue, and high biocompatibility through the synergistic design of the composite skin layer and the three-layer functional core layer. The composite skin layer uses sodium alginate as the gel skeleton, and is compounded with polydopamine and chitosan to improve the interface bonding and biocompatibility; the three-layer core layer adopts a hybrid system of carbon material-conductive polymer-nanomaterial, taking into account the conductivity and mechanical stability; after three-core spinning, solidification and curing processes, it is suitable for nerve electrophysiological signal acquisition.
[0042] II. Example 1: Preparation of gel probe with standard parameters
[0043] S1. Preparation of composite skin layer spinning solution
[0044] Take 1000 mL of deionized water, add 20 g of sodium alginate (to form a three-dimensional gel network as the basic skeleton of the skin layer), stir at 35°C for 1 hour until completely dissolved, and the solution is viscous. Add 10 g of polydopamine (containing catechol groups, which can form covalent bonds with the core layer material to enhance the interfacial bonding force between the skin layer and the core layer), continue to stir for 15 hours, during which the polydopamine is uniformly dispersed and the functional groups are activated. Add 5 g of chitosan (degree of deacetylation 90%, molecular weight 60000 Da, with amino groups to improve the affinity of the skin layer to biological tissues), 15 g of chondroitin sulfate (molecular weight 40000 Da, inhibits the release of inflammatory factors and reduces tissue rejection after implantation), and 8 g of polyethylene oxide (molecular weight 250000 Da, long-chain structure increases the toughness of the skin layer to avoid brittle fracture), stir at 25°C for 10 hours to obtain a uniform spinning solution with a viscosity of .
[0045] S2. Preparation of the first core layer spinning solution
[0046] Take 500mL of deionized water, add 5g of carbon nanotubes (aspect ratio 70, the tubular structure forms a conductive path, providing basic conductivity for the core layer), and ultrasonicate at 300W power for 4 hours to break up the agglomerates and disperse the individual tubes. Add 10g of polyaniline (conductivity 100S / cm, the conjugated structure enhances charge transfer efficiency). Nanosheets (thickness 1.0 nm, layered structure filling the gaps between carbon nanotubes and improving the mechanical strength of the core layer), 40 g of ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate (reducing the interface resistance between carbon nanotubes and polyaniline and promoting uniform dispersion), stirred at 30 ° C for 12 hours to obtain a black uniform spinning solution.
[0047] S3. Preparation of the second core layer spinning solution
[0048] To 500 mL of deionized water, 5 g of graphene (8 μm diameter, 2 layers, two-dimensional structure providing a large-area conductive network) was added. Ultrasonication was performed at 250 W for 3 hours to obtain a monolayer dispersion. Then, 10 g of polypyrrole (80 S / cm conductivity, forming a conductive synergistic relationship with graphene), 1.5 g of boron nitride nanosheets (2 μm lateral size, 4 layers, insulating properties to reduce signal crosstalk between core layers), and 25 g of the ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate (to enhance the stability of graphene in solution) were added. The mixture was stirred at 30°C for 12 hours to obtain a gray-black spinning solution.
[0049] S4. Preparation of the third core layer spinning solution
[0050] Take 500mL of deionized water and add 5g of MXene ( The 2nm-thick sheet, containing functional groups such as hydroxyl groups on the surface, combines high conductivity with biocompatibility. Ultrasonic treatment at 250W power for 3 hours maintained the integrity of the sheet structure. Then, 10g of polythiophene (conductivity 60S / cm, forming continuous conductive chains with the MXene), 1.5g of hydroxyapatite nanocrystals (aspect ratio 4, particle size 80nm, composition similar to bone tissue, enhancing interfacial compatibility between the core layer and biological tissue), and 20g of the ionic liquid 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (to inhibit the restacking of the MXene sheets) were added. The mixture was stirred at 30°C for 12 hours to obtain a brown-black spinning solution.
[0051] S5. Three-core spinning
[0052] A transverse coaxial needle (outer tube inner diameter 280 pm, middle tube inner diameter 150 pm, inner tube inner diameter 100 pm, length ratio 1:0.8:0.7) was used, with an outer tube and middle tube spacing of 90 pm and a middle tube and inner tube spacing of 50 pm to ensure clear boundaries between layers. The composite skin layer spinning solution was injected into the outer tube, the first core layer solution was injected into the outer layer of the middle tube, the second core layer solution was injected into the middle layer of the middle tube, and the third core layer solution was injected into the inner tube, with an extrusion speed of 1.2 mL / h. The coagulation bath was an aqueous solution containing 8 wt% calcium chloride (to quickly crosslink sodium alginate into a gel to fix the skin-core structure), 2 wt% dopamine (to promote crosslinking of polydopamine and chitosan inside the skin layer), and 2 wt% magnesium chloride (to adjust the gel rate and avoid skin layer shrinkage), with a temperature of 25°C and a stirring speed of 150 r / min to ensure uniform stress on the fiber, resulting in a diameter of 180 pm of the nascent fiber.
[0053] S6. Stretching and solidification
[0054] The nascent fiber was passed through a 2 m solidification channel at a speed of 10 cm / min, with a 4 wt% calcium chloride solution in the channel (to further strengthen the crosslinking of the skin layer and improve the structural stability), a temperature of 38°C, and segmented temperature control (first segment 30°C, second segment 38°C, third segment 40°C, length ratio 1:2:1) to gradually enhance crosslinking and avoid skin layer cracking. The draw ratio was 1.4 times (to promote the ordered arrangement of the core layer conductive material along the fiber axis, improving electrical conductivity), and the solidification time was 25 minutes, resulting in a solidified fiber.
[0055] S7. Washing and drying
[0056] The solidified fiber was washed with deionized water 5 times (10 minutes each time to remove residual calcium chloride and other electrolytes to avoid affecting biocompatibility), and vacuum dried at 38°C for 20 hours (to remove moisture, fix the fiber size, and prevent subsequent swelling and deformation).
[0057] S8. Surface modification
[0058] A 50 vol% ethanol solution of 0.4 wt% polyethylene glycol (molecular weight 5000 Da) was prepared, and 0.1 wt% succinimidyl ester activator was added (to form covalent bonds between polyethylene glycol and the amino groups of the skin layer), and the pH was adjusted to 7.2. The dried fiber was immersed in the solution, and ultrasonic treatment was performed at 25°C for 3 hours (power 250 W to promote uniform coverage of the skin layer surface with polyethylene glycol), and the fiber was washed with ethanol 5 times (to remove unbound polyethylene glycol), and vacuum dried at 38°C for 12 hours, resulting in a surface-modified gel probe.
[0059] III. Example 2: Preparation with high-conductive core layer ratio
[0060] S1. Preparation of composite skin layer spinning solution
[0061] Take 1000 mL of deionized water, add 20 g of sodium alginate (form a three-dimensional gel network as the basic skeleton of the skin layer), stir at 35°C for 1 hour to completely dissolve, the solution is viscous. Add 10 g of polydopamine (containing catechol groups, can form covalent bond with core layer material, enhance the interface bonding force between skin layer and core layer), continue to stir for 15 hours, during which the polydopamine is uniformly dispersed and the functional groups are activated. Add 5 g of chitosan (degree of deacetylation 90%, molecular weight 60000 Da, with amino groups, improve the affinity of the skin layer to biological tissues), 18 g of chondroitin sulfate (molecular weight 40000 Da, increase the amount of anti-inflammatory ingredients, further inhibit the release of inflammatory factors, reduce tissue rejection after implantation), 10 g of polyethylene oxide (molecular weight 250000 Da, long chain structure improves the flexibility of the skin layer, increases the toughness of the skin layer, avoids brittle fracture), stir at 25°C for 10 hours to obtain a uniform spinning solution, the viscosity is close to (due to component fine-tuning, there may be slight differences).
[0062] S2. First core layer spinning solution preparation
[0063] Take 500 mL of deionized water, add 6 g of carbon nanotubes (aspect ratio 70, increase the proportion of conductive substrate, tubular structure forms more intensive conductive path, provides better conductivity for the core layer), ultrasonic at 300 W for 4 hours, break the agglomeration to make single dispersion. Add 12 g of polyaniline (conductivity 100 S / cm, conjugated structure enhances charge transfer efficiency, increase the amount to improve the conductivity), 45 g of ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate (reduce the interface resistance between carbon nanotubes and polyaniline, promote uniform dispersion), stir at 30°C for 12 hours to obtain a black uniform spinning solution, enhance the conductivity of the core layer.
[0064] S3. Second core layer spinning solution preparation
[0065] Take 500 mL of deionized water, add 6 g of graphene (flaky diameter 8 μm, number of layers 2, increase the proportion of conductive substrate, two-dimensional structure provides larger area conductive network), ultrasonic at 250 W for 3 hours to obtain a single layer dispersion. Add 12 g of polypyrrole (conductivity 80 S / cm, forms a conductive synergy with graphene, increase the amount to enhance the conductive effect), 1.8 g of boron nitride nanosheet (lateral size 2 μm, number of layers 4, insulation characteristics reduce signal crosstalk between core layers), 30 g of ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate (improve the stability of graphene in solution), stir at 30°C for 12 hours to obtain a gray-black spinning solution.
[0066] S4. Third core layer spinning solution preparation
[0067] Take 500mL of deionized water and add 6g of MXene ( The sheet thickness is 2 nm, and the conductive substrate is increased in proportion. The surface contains functional groups such as hydroxyl groups, achieving both high conductivity and biocompatibility. Ultrasonication at 250 W power is applied for 3 hours to maintain the integrity of the sheet structure. 12 g of polythiophene (conductivity 60 S / cm, forming continuous conductive chains with the MXene; increasing the dosage improves conductivity), 1.8 g of hydroxyapatite nanocrystals (aspect ratio 4, particle size 80 nm, composition similar to bone tissue, enhancing interfacial compatibility between the core layer and biological tissue), and 25 g of the ionic liquid 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (to inhibit restacking of the MXene sheets) are added. Stirring at 30°C for 12 hours yields a brownish-black spinning solution.
[0068] S5. Three-core spinning
[0069] A transverse coaxial needle (outer tube inner diameter 280μm, middle tube inner diameter 150μm, inner tube inner diameter 100μm, length ratio 1:0.8:0.7) was used. The spacing between the outer and middle tubes was 90μm, and the spacing between the middle and inner tubes was 50μm, ensuring clear boundaries between the layers. The composite sheath spinning solution was injected into the outer tube, the first core layer solution into the outer layer of the middle tube, the second core layer solution into the middle layer of the middle tube, and the third core layer solution into the inner tube at an extrusion rate of 1.2mL / h. The coagulation bath consisted of an aqueous solution containing 8wt% calcium chloride (to rapidly crosslink the sodium alginate into a gel and stabilize the sheath-core structure), 2wt% dopamine (to promote crosslinking between polydopamine and chitosan within the sheath), and 2wt% magnesium chloride (to regulate the gelation rate and prevent sheath shrinkage). The temperature was 28°C (to accelerate sheath solidification) and the stirring speed was 150r / min to ensure uniform fiber stress. As-spun fibers with a diameter approaching 180μm were obtained (may vary slightly due to composition and process adjustments).
[0070] S6. Drawing and curing
[0071] The spun fibers were passed through a 2-meter curing tunnel at a speed of 10 cm / min. The tunnel contained a 4wt% calcium chloride solution (to further strengthen cortical crosslinking and enhance structural stability). The temperature was 38°C, with staged temperature control (first stage 30°C, second stage 38°C, third stage 40°C, with a length ratio of 1:2:1) to gradually enhance crosslinking and prevent cortical cracking. The draft ratio was 1.4x (to encourage the core conductive material to align along the fiber axis, improving conductivity). The curing time was 25 minutes, yielding the cured fibers.
[0072] S7.Washing and drying
[0073] The cured fibers were washed five times with deionized water (10 min each time to remove residual electrolytes such as calcium chloride and avoid affecting biocompatibility) and dried in a vacuum at 38 °C for 20 h (to remove moisture, fix the fiber size, and prevent subsequent swelling and deformation).
[0074] S8. Surface modification
[0075] A 0.4 wt% polyethylene glycol (MW 5000 Da) solution in 50 vol% ethanol was prepared, along with 0.1 wt% succinimide ester activator (to form covalent bonds between the polyethylene glycol and the amino groups of the cortex). The pH was adjusted to 7.2. The dried fiber was immersed in the solution and sonicated at 18 kHz for 3 hours at 25°C (250 W to promote uniform coverage of the cortex surface with polyethylene glycol). The fiber was then washed five times with ethanol to remove unbound polyethylene glycol and dried under vacuum at 38°C for 12 hours to obtain the surface-modified gel probe.
[0076] Example 3: Optimized preparation with high biocompatibility
[0077] S1. Preparation of composite cortex spinning solution
[0078] Take 1000mL of deionized water, add 20g of sodium alginate (to form a three-dimensional gel network as the basic skeleton of the cortex), stir at 35℃ for 1 hour until completely dissolved, and the solution becomes viscous. Add 10g of polydopamine (containing catechol groups, which can form covalent bonds with the core layer material to enhance the interfacial bonding between the cortex and the core layer), and continue stirring for 15 hours. During this period, the polydopamine is evenly dispersed and the functional groups are activated. Add 7g of chitosan (90% deacetylation degree, molecular weight 60,000Da, to increase biocompatibility components, with its own amino groups, to further enhance the affinity between the cortex and biological tissues), 20g of chondroitin sulfate (molecular weight 40,000Da, to inhibit the release of inflammatory factors and reduce tissue rejection after implantation), and 8g of polyethylene oxide (molecular weight 250,000Da, the long chain structure increases the toughness of the cortex and avoids brittle fracture) in sequence. Stir at 25℃ for 10 hours to obtain a uniform spinning solution with a viscosity close to (There may be slight differences due to minor adjustments in ingredients).
[0079] S2. Preparation of the first core layer spinning solution
[0080] Take 500mL of deionized water, add 5g of carbon nanotubes (aspect ratio 70, the tubular structure forms a conductive path, providing basic conductivity for the core layer), and ultrasonicate at 300W power for 4 hours to break up the agglomerates and disperse the individual tubes. Add 10g of polyaniline (conductivity 100S / cm, the conjugated structure enhances charge transfer efficiency). Nanosheets (thickness 1.0 nm, layered structure filling the gaps between carbon nanotubes and improving the mechanical strength of the core layer), 36 g of ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate (reduced by 10% to reduce potential toxicity, while reducing the interface resistance between carbon nanotubes and polyaniline and promoting uniform dispersion), stirred at 30°C for 12 hours to obtain a black uniform spinning solution.
[0081] S3. Preparation of the second core layer spinning solution
[0082] To 500 mL of deionized water, 5 g of graphene (8 μm diameter, 2 layers, two-dimensional structure providing a large-area conductive network) was added. Ultrasonication was performed at 250 W for 3 hours to obtain a monolayer dispersion. Then, 10 g of polypyrrole (80 S / cm conductivity, forming a conductive synergistic relationship with graphene), 1.5 g of boron nitride nanosheets (2 μm lateral size, 4 layers, insulating properties to reduce signal crosstalk between core layers), and 22.5 g of the ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate (reducing the amount by 10% to reduce potential toxicity and improve the stability of graphene in solution) were added. The mixture was stirred at 30°C for 12 hours to obtain a gray-black spinning solution.
[0083] S4. Preparation of the third core layer spinning solution
[0084] Take 500mL of deionized water and add 5g of MXene ( The 2nm-thick sheet, containing functional groups such as hydroxyl groups on the surface, combines high conductivity with biocompatibility. Ultrasonication at 250W power for 3 hours maintained the integrity of the sheet structure. Then, 10g of polythiophene (conductivity 60S / cm, forming continuous conductive chains with MXene), 2g of hydroxyapatite nanocrystals (aspect ratio 4, particle size 80nm; increasing the dosage makes the composition closer to bone tissue, improves tissue affinity, and enhances interfacial adaptation between the core layer and biological tissue) and 18g of the ionic liquid 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (reducing the dosage by 10% to reduce potential toxicity and inhibit restacking of the MXene sheets) were added. Stirring at 30°C for 12 hours yielded a brown-black spinning solution.
[0085] S5. Three-core spinning
[0086] A transverse coaxial needle (outer tube inner diameter 280 μm, middle tube inner diameter 150 μm, inner tube inner diameter 100 μm, length ratio 1:0.8:0.7) was used. The spacing between the outer and middle tubes was 90 μm, and the spacing between the middle and inner tubes was 50 μm, ensuring clear boundaries between the layers. The composite sheath spinning solution was injected into the outer tube, the first core layer solution into the outer layer of the middle tube, the second core layer solution into the middle layer of the middle tube, and the third core layer solution into the inner tube at an extrusion rate of 1.2 mL / h. The coagulation bath consisted of an aqueous solution containing 8 wt% calcium chloride (to rapidly crosslink the sodium alginate into a gel and stabilize the sheath-core structure), 2 wt% dopamine (to promote crosslinking between polydopamine and chitosan within the cortex), and 3 wt% magnesium chloride (increased to 3 wt% to slow the gelation rate and reduce stress within the cortex). The temperature was 25°C and the stirring speed was 150 rpm to ensure uniform fiber stress. As-spun fibers with a diameter of 180 μm were obtained.
[0087] S6. Drawing and curing
[0088] The nascent fiber was passed through a 2 m curing channel at a speed of 10 cm / min, the channel contained a 4 wt% calcium chloride solution (to further strengthen the cross-linking of the skin layer and improve the structural stability), the temperature was 38℃, and the temperature was controlled in sections (the first section was 30℃, the second section was 38℃, and the third section was 40℃, and the length ratio was 1:2:1), and the cross-linking was gradually enhanced to avoid cracking of the skin layer. The draw ratio was 1.4 times (to promote the ordered arrangement of the core layer conductive material along the fiber axis, and improve the electrical conductivity), and the curing time was 25 minutes, to obtain the cured fiber.
[0089] S7. Washing and drying
[0090] The cured fiber was washed with deionized water for 5 times (10 minutes each time, to remove residual calcium chloride and other electrolytes, and to avoid affecting biocompatibility), and was vacuum dried at 38℃ for 20 hours (to remove moisture, fix the fiber size, and prevent subsequent swelling and deformation).
[0091] S8. Surface modification
[0092] A 50 vol% ethanol solution of 0.5 wt% polyethylene glycol (molecular weight 5000 Da, concentration increased to 0.5 wt%, to improve protein adsorption resistance) was prepared, and 0.1 wt% succinimidyl ester activator (to form covalent bonds between polyethylene glycol and the amino groups of the skin layer) was added, and the pH was adjusted to 7.2. The dried fiber was immersed in the solution, and was treated with 18 kHz ultrasound at 25℃ for 3 hours (power 250 W, to promote uniform coverage of the skin layer surface with polyethylene glycol), and was washed with ethanol for 5 times (to remove unbound polyethylene glycol), and was vacuum dried at 38℃ for 12 hours, to obtain the surface-modified gel probe.
[0093] V. Comparative Example: Traditional Single-Core Structure Probe
[0094] S1. Preparation of skin layer spinning solution
[0095] 1000 mL of deionized water was taken, 20 g of sodium alginate was added, and stirring was performed at 35℃ for 1 hour, to obtain a single skin layer spinning solution (without biocompatibility optimization components).
[0096] S2. Preparation of core layer spinning solution
[0097] 500 mL of deionized water was taken, 10 g of graphene oxide was added, and ultrasonic treatment was performed for 3 hours, to obtain a single core layer spinning solution (without conductive polymer and nanomaterial reinforcement).
[0098] S3. Single-core spinning formation
[0099] A coaxial needle (outer tube inner diameter 300 μm, inner tube inner diameter 150 μm) was used, the skin layer liquid and the core layer liquid were injected into the outer tube and the inner tube respectively, the extrusion speed was 10 μL / min and 5 μL / min, and the coagulation bath was a 5 wt% calcium chloride solution (without interface reinforcement components), and coagulation was performed at 25℃ for 10 minutes.
[0100] S4. Reduction and drying
[0101] The fibers were reduced with 1 mL of hydrazine hydrate at 95℃ for 1 hour, washed with water-ethanol mixture, and dried at 90℃ to obtain the single-core structure probe.
[0102] The performance comparison results of the examples and the comparative examples are as follows:
[0103] Table 1
[0104]
[0105] The surface impedance of Examples 1-3 is significantly lower than that of the comparative examples, and the multi-conductive channels of the three-core structure and the synergistic effect of the hybrid material solve the high impedance problem of the traditional probe; the conductivity reaches 90-110 S / cm, which is better than 50 S / cm of the comparative examples, confirming the conductive advantage of the carbon material-conductive polymer-nanomaterial system. The Young's modulus of the examples matches the soft tissue, and the elongation at break is much higher than that of the comparative examples, avoiding mechanical damage during implantation, while the single structure of the comparative examples is obviously mechanically mismatched. In terms of biocompatibility, the cell survival rate of the examples is ≥95% due to the components such as chitosan and chondroitin sulfate, and the comparative examples lack biocompatibility design, and the performance gap is significant.
[0106] Although the embodiments of the present application have been shown and described, it can be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A biocompatible gel probe based on three-core spinning technology, characterized in that: The gel probe comprises a composite cortex and a three-layer functional core layer. The composite cortex is composed of a sodium alginate-polydopamine-chitosan graft copolymer, and the mass ratio of sodium alginate, polydopamine and chitosan is 2:1:0.
5. Chondroitin sulfate and Polyethylene oxide; sodium alginate provides a gel network skeleton for the cortex, polydopamine enhances the interfacial bonding between the cortex and the core layer through catechol groups, chitosan improves the biocompatibility of the cortex, chondroitin sulfate reduces inflammatory responses, and polyethylene oxide enhances the flexibility of the cortex; The three functional core layers are the first core layer carbon nanotube-polyaniline Nanosheet hybrid material, second core layer graphene-polypyrrole-boron nitride nanosheet hybrid material and third core layer Polythiophene-hydroxyapatite nanocrystalline hybrid material, the mass ratio of carbon material, conductive polymer and new nanomaterial in each core layer is 1:2:0.3; carbon nanotubes, graphene and MXene are used as the core conductive matrix, polyaniline, polypyrrole and polythiophene enhance the conductivity of the core layer, Nanosheets, boron nitride nanosheets, and hydroxyapatite nanocrystals synergistically enhance the mechanical strength and conductive stability of the core layer; The diameter ratio of the skin layer to the three-layer core layer is 1:0.28:0.22:0.17; The deacetylation degree of chitosan in the composite cortex is ≥90%, and the molecular weight is 50,000-80,000 Da; the molecular weight of chondroitin sulfate is 30,000-50,000 Da, and the molecular weight of polyethylene oxide is 200,000-300,000 Da; The aspect ratio of carbon nanotubes in the first core layer is 50-100, and the thickness of MoS2 nanosheets is 0.8-1.2nm; the diameter of graphene sheets in the second core layer is 5-10μm, and the lateral size of boron nitride nanosheets is 1-3μm; the MXene in the third core layer is , the aspect ratio of hydroxyapatite nanocrystals is 3-5.
2. The biocompatible gel probe based on three-core spinning technology according to claim 1, characterized in that: Composite cortex thickness 70-90μm, sodium alginate viscosity , used to maintain the stability of the gel structure; the diameter of the first core layer is 25-30μm, the diameter of the second core layer is 20-25μm, the diameter of the third core layer is 15-20μm, and the overall diameter is 150-200μm, which is adapted to the size of neurons.
3. The biocompatible gel probe based on three-core spinning technology according to claim 1, characterized in that: The conductivity of the first core layer is 80-120S / cm, the conductivity of the second core layer is 70-100S / cm, and the conductivity of the third core layer is 50-80S / cm; the Young's modulus of the gel probe is 1.0-1.8MPa, matching the mechanical properties of soft tissue, and the elongation at break , to avoid breakage during implantation.
4. The biocompatible gel probe based on three-core spinning technology according to claim 1, characterized in that: The purity of the nanosheets is ≥99%, which is used to reduce the interference of impurities on conductivity. The number of boron nitride nanosheets is 3-5 layers, which enhances the insulation barrier of the core layer. The particle size of the hydroxyapatite nanocrystals is 50-100nm; the degree of polymerization of the conductive polymer in each core layer is 500-1000.
5. The biocompatible gel probe based on three-core spinning technology according to claim 1, characterized in that: The surface is modified with a polyethylene glycol layer with a molecular weight of 4000-6000Da, which is connected to the cortex through a succinimide ester bond. The water contact angle after modification is 30-40 degrees, which reduces protein adsorption and the modification density. , improve anticoagulant properties.
6. The biocompatible gel probe based on three-core spinning technology according to claim 1, characterized in that: The swelling degree of the composite skin layer is 200%-300%, maintaining a moist environment, and the degradation rate in phosphate buffer solution is ≤5% within 24 hours; the core layer material has a 24-hour stability of ≥95% under the same conditions.
7. A method for preparing a biocompatible gel probe based on three-core spinning technology according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Preparation of composite cortex spinning solution: Sodium alginate is dissolved in deionized water. Stir for 1 hour to form the initial gel network, add Polydopamine was stirred for 15 hours to activate the catechol groups, and then added Chitosan, Chondroitin sulfate and Polyethylene oxide, Stir for 10 hours to evenly disperse the components and obtain a uniform spinning solution; S2. Preparation of the first core layer spinning solution: Carbon nanotubes were dispersed in deionized water, ultrasonicated for 4 hours to break up the agglomerates, and then added Polyaniline and Nanosheets The ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate was stirred at 30°C for 12 hours. The ionic liquid promoted the dispersion of the conductive material and the interfacial bonding. S3. Preparation of the second core layer spinning solution: Graphene was dispersed in deionized water and ultrasonicated for 3 hours to obtain a monolayer dispersion. Polypyrrole, Boron nitride nanosheets and The ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate was stirred at 30°C for 12 hours, and the boron nitride nanosheets isolated the conductive areas to reduce signal interference; S4. Preparation of the third core layer spinning solution: Dispersed in deionized water, ultrasonicated for 3 hours to maintain the lamellar structure, added Polythiophene, Hydroxyapatite nanocrystals and The ionic liquid 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt was stirred at 30°C for 12 hours to enhance the interface adaptation of the core layer with biological tissues by hydroxyapatite nanocrystals; S5. Three-core spinning: using a transverse coaxial needle, the inner diameter of the outer tube is 280μm, the inner diameter of the middle tube is 150μm, and the inner diameter of the inner tube is 100μm. The length ratio of the outer tube, middle tube and inner tube is 1:0.8:0.7; the skin layer spinning solution is injected into the outer tube, the first core layer solution is injected into the outer layer of the middle tube, the second core layer solution is injected into the middle layer of the middle tube, and the third core layer solution is injected into the inner tube. The extrusion speed is 2000 rpm. ; Coagulation bath contains calcium chloride, Dopamine and Magnesium chloride, temperature 25°C, and calcium chloride promote rapid gel formation in the cortex, while dopamine enhances cortical cross-linking; S6. Drawing and curing: The nascent fiber passes through a 2m curing channel at a speed of 10cm / min. Calcium chloride solution, temperature 38°C, draft ratio 1.4 times, curing time 25 minutes, drafting improves the orderliness of the conductive material in the core layer, and high temperature promotes the interface reaction between the skin and the core layer; S7. Washing and Drying: Wash five times with deionized water to remove residual salts, and vacuum dry at 38°C for 20 hours to fix the structure. S8. Surface modification: Soak the dried probe in polyethylene glycol Ethanol solution, pH 7.2, 18kHz ultrasound at 25°C for 3 hours, ethanol assisted polyethylene glycol penetration, and ultrasound promoted uniform coverage of the modified layer; washed with ethanol 5 times, and vacuum dried at 38°C for 12 hours to form a stable modified layer.
8. The method for preparing a biocompatible gel probe based on three-core spinning technology according to claim 7, characterized in that: In step S5, the distance between the outer tube and the middle tube of the transverse coaxial needle is 90 μm, and the distance between the middle tube and the inner tube is 50 μm to ensure uniform wrapping of each layer. The stirring speed of the coagulation bath is 150 r / min to ensure uniform force on the fiber.
9. The method for preparing a biocompatible gel probe based on three-core spinning technology according to claim 7, characterized in that: In step S6, the flow rate of the solution in the curing channel is 0.6 m / min, and segmented temperature control is adopted: the first segment is 30°C, the second segment is 38°C, and the third segment is 40°C. The length ratio of each segment is 1:2:
1. The segmented temperature control gradually enhances crosslinking to avoid structural damage.
10. The method for preparing a biocompatible gel probe based on three-core spinning technology according to claim 7, characterized in that: In step S8, the polyethylene glycol solution contains Succinimide ester activator promotes covalent binding with the cortex, ultrasonic power of 250W improves modification efficiency, and the zeta potential of the probe surface after modification is -20 to -15mV.
Citation Information
Patent Citations
Conductive fiber bundle composite hydrogel material with three-stage nested structure and preparation method of conductive fiber bundle composite hydrogel material
CN116077727A
Wet-spun radiative cooling fiber, preparation method, and use thereof
WO2022148401A1